Management Policy for Oil and Gas Sector of Bojonegoro Regency Government in Kang Yoto Era - Agus Danugroho; Fitria Yusfira (Institut Pemerintahan Dalam Negeri, 2023)
This study aims to understand policy strategies employed by the